Relationship between Sustained Reductions in Plasma Lipid and Lipoprotein Concentrations with Apheresis and Plasma Levels and mRNA Expression of PTX3 and Plasma Levels of hsCRP in Patients with HyperLp(a)lipoproteinemia - Claudia Stefanutti; Fabio Mazza; Michael Steiner; Gerald F. Watts; Joel De Nève; Daniela Pasqualetti; Juergen Paal (Mediators of Inflammation)
The effect of lipoprotein apheresis (Direct Adsorption of Lipids, DALI) (LA) on plasma levels of pentraxin 3 (PTX3), an inflammatory marker that reflects coronary plaque vulnerability, and expression of PTX3 mRNA was evaluated in patients with hyperLp(a)lipoproteinemia and angiographically defined atherosclerosis/coronary artery disease. Eleven patients, aged 55±9.3 years (mean ± SD), were enrolled in the study. PTX3 soluble protein levels in plasma were unchanged by 2 sessions of LA; however, a downregulation of mRNA expression for PTX3 was observed, starting with the first session of LA (p<0.001). The observed reduction was progressively increased in the interval between the first and second LA sessions to achieve a maximum decrease by the end of the second session. A statistically significantly greater treatment-effect correlation was observed in patients undergoing weekly treatments, compared with those undergoing treatment every 15 days. A progressive reduction in plasma levels of C-reactive protein was also seen from the first session of LA, with a statistically significant linear correlation for treatment-effect in the change in plasma levels of this established inflammatory marker (R2=0.99; p<0.001). Our findings suggest that LA has anti-inflammatory and endothelium protective effects beyond its well-established efficacy in lowering apoB100-containing lipoproteins.